A Gigantic Anogenital Lesion: Buschke-Lowenstein Tumor - Rikinder Sandhu; Zaw Min; Nitin Bhanot (Case Reports in Dermatological Medicine)
Buschke-Lowenstein tumor is a relatively rare sexually transmitted disease. It is a neoplasm of the anogenital region which has benign appearance on histopathology but is locally destructive. It carries a high recurrence rate and a significant potential for malignant transformation. Human papilloma virus has been implicated as an etiologic agent for this tumor. Since this disease is rare and no controlled studies exist, radical excision of this anogenital lesion is generally recommended as the first line therapy and close vigilance and followup are essential. We have discussed an overview of etiopathogenesis, clinical presentation, diagnosis, and management of this uncommonly encountered disease.